BREGZIT IMPACT ON SERBIAN ECONOMIC DEVELOPMENT - Stošić Mihajlović, Ljiljana (Journal of process management and new technologies, 2016)
On Thursday, 23.6.2016. the British were out to vote - a referendum to stay or exit from European Union nations. With minimal but sufficient majority pleaded United Kingdom leave European Union. The paradox is even greater because there are, the principles, and the chapters that each member state has to pass, and to harmonize its legislation and rules of good practice in force in the EU, but there are no rules to carry out, or how to handle the situation when the country decided by a majority vote of its population to leave the EU. However, what is for Serbia at this moment most important is how it will affect the flow Bregzit and Serbia’s path towards the EU, in terms of whether and how much will be the consequences for Serbia in the light of recent events. More important question is, it seems, refers to economic stability in Serbia. In this regard, the paper discusses the situation primarily on the economic front Serbia after the decision of Great Britain to leave the European Union. Special attention is paid to the opportunities that presented themselves in connection with a faster reception of Serbia in the EU or in the work also indicates the obstacles that Serbia will inevitably encounter on the road to the EU as a strategic orientation through and in a situation where the purpose and existence of the European Union questioned. However, the conclusion is that the citizens of Serbia needed strong EU compared to the one that has ever existed.